Hydrochemical study of wetlands in a Cerrado watershed at Minas Gerais State, Brazil - Quirino, R. C. [UNESP]; Bonotto, D. M. [UNESP]; Rosolen, V. [UNESP] (Springer Nature, 2025)
The Triângulo Mineiro Sedimentary Plateau harbors an important wetland system, comprising one of the remaining vegetal physiognomies of the Brazilian Cerrado. Such a region is one of the greatest grain-producing areas of Brazil, in which soy and sugar cane are the main crops. In this study, hydrochemical analyses were performed to determine the chemical composition of wetland waters occurring at the Claro River watershed, Uberaba city, Minas Gerais State, to identify possible impacts related to intensive agricultural activities in the region. Most of the waters are classified as sodium bicarbonate type, influenced by the transformation of carbon dioxide into bicarbonate and the low concentration of cations. The waters present some similarity with rainfall composition, mainly in the anionic content, evidencing the rain contribution in wetland waters. The rainwater contribution could not be observed in the trace elements data, whose enrichment in the system occurs due to changes and complexation in soil and soil solution, mainly aligned with the reduction of iron and manganese hydroxides, typical processes occurring in hydromorphized areas. Concerning the water quality, most of the samples analyzed were under the guidelines established by Brazilian legislation and the World Health Organization (WHO). The main exception in some monitoring points is the dissolved iron concentration that surpassed the reference level of 0.3 mg/L as proposed in 2011 by the WHO. Its presence in the wetland waters could be associated with the Fe crust dismantling, among other factors.